An intimate evening [compact disc] - Foster, David, 1949- (Decca, 2019)
David Foster performs songs from his unparalleled catalog along with friends such as Katharine McPhee, Pia Toscano, Loren Allred, and more. Revisit hits like The Power of Love; The Prayer; songs from The Bodyguard; and so many more.